Rythmes et pratiques de la métallurgie du fer aux xive et xve siècles : les « bloomeries » de Tudeley (Kent) et de Byrkeknott (comté de Durham) - Danielle Arribet-Deroin (Archéologie Médiévale)
Accounts from the English forges of Tudeley (1329-1354) and Byrkeknott (1408-1409) provide very practical information on how forges worked during the Late Middle Ages. We learn of the make-up of the workshops and the processes that took place there : roasting and reduction at Tudeley, reduction and bloom smithing at Byrkeknott where hydraulic energy was used, probably to drive the furnace bellows. There was an intensive bloom production rhythm of five or six per week, though at Tudeley the number of weeks worked per year was irregular. Estimates of supplies and production are put forward ; the tasks of the ironworkers and their wages are described, as is the construction and starting up of the Byrkeknott forge. These documents enable us to compare the manual forge with the mechanized forge, and stimulate interchange with fieldwork and experimentation specialists.